Governance of picture archiving and communications systems : data security and quality management of filmless radiology - Tong, Carrison K. S., 1962-; Wong, Eric T. T. (Eric Tsun Tat) (Hershey, PA : Medical Information Science Reference, 2009)
'This book examines information security management for the facilitation of picture archiving and communication systems'--Provided by publisher
'Premier reference source'--Cover
Includes bibliographical references and index
Keywords: Picture archiving and communication systems in medicine -- Security measures; Picture archiving and communication systems in medicine -- Quality control